2014
DOI: 10.1113/jphysiol.2013.265108
|View full text |Cite|
|
Sign up to set email alerts
|

In vivo and in vitro biophysical properties of hair cells from the lateral line and inner ear of developing and adult zebrafish

Abstract: Hair cells detect and process sound and movement information, and transmit this with remarkable precision and efficiency to afferent neurons via specialized ribbon synapses. The zebrafish is emerging as a powerful model for genetic analysis of hair cell development and function both in vitro and in vivo. However, the full exploitation of the zebrafish is currently limited by the difficulty in obtaining systematic electrophysiological recordings from hair cells under physiological recording conditions. Thus, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
120
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(130 citation statements)
references
References 66 publications
(166 reference statements)
8
120
2
Order By: Relevance
“…Adult zebrafish are used in a variety of auditory studies, including research on hair cell death and putative mechanisms of regeneration (Bang et al, 2002; Schuck et al, 2011; Liang et al, 2012, Burns et al, 2013; Uribe et al, 2013a). In particular, a recent study demonstrated that biophysical hair cell properties are mature in zebrafish over two months old, suggesting that adult animals are preferable for some auditory physiology experiments (Olt et al, 2014). Our data show that care is needed in selecting a fish line for auditory studies and in comparing results between fish lines, particularly for research using adult animals.…”
Section: Discussionmentioning
confidence: 99%
“…Adult zebrafish are used in a variety of auditory studies, including research on hair cell death and putative mechanisms of regeneration (Bang et al, 2002; Schuck et al, 2011; Liang et al, 2012, Burns et al, 2013; Uribe et al, 2013a). In particular, a recent study demonstrated that biophysical hair cell properties are mature in zebrafish over two months old, suggesting that adult animals are preferable for some auditory physiology experiments (Olt et al, 2014). Our data show that care is needed in selecting a fish line for auditory studies and in comparing results between fish lines, particularly for research using adult animals.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the development of a loose patch method of recording spiking activity in afferent neurons of the lateral line organ has been instrumental in describing defects in various mutants (Trapani and Nicolson, 2010). Moreover, new methods for quantifying calcium transients in zebrafish hair cells (Kindt et al, 2012) have made valuable contributions to understanding mutant phenotypes, and finally, the ability to directly measure hair-cell currents and capacitance using patch clamp recordings in larvae (Olt et al, 2014; Ricci et al, 2013) opens the door to more detailed analysis in future studies.…”
Section: Functional Aspects Of Ribbon Synapsesmentioning
confidence: 99%
“…Thus, another type of recording was recently established in zebrafish larvae: whole-cell recordings of lateral-line hair cells (Olt et al, 2014, 2016a, 2016b; Ricci et al, 2013). The technique is challenging and to date, direct measurements of mechanotransduction currents are sparse, but further use and development of this method will be critical for characterizing different types of currents in various mutants.…”
Section: Introductionmentioning
confidence: 99%